THE EFFECT OF HEDONIC MOTIVES AND SHOP ENVIRONMENT ON IMPULSE BUYING IN MANADO TOWARDS RETAILER STORES (CASE AT MATAHARI DEPT. STORE) - Tikker, Aprilyan Bionita; Pandowo, Merinda (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2016)
Impulse Buying is the thing that has been an interesting topic to analyze, since it always happens in daily lives of almost everyone. In Manado, the number of shopping centers has increased rapidly. This condition is supported by the consumptive behavior of people in Manado. People in Manado and around it give a good response to the existence of shopping centers. It can be seen from the big number of people who fulfill malls and the other shopping centers every day. The purpose of this research is to analyze the effect of Hedonic Motives and Shop Environment on Impulse Buying in Manado towards Retailer Stores. The population observed is people who have purchased impulsively at Matahari Department Store Manado with 100 respondents as sample. This research uses quantitative analysis by using questionnaires and uses Multiple Regression Analysis. The conclusion is hedonic motives and shop environment influence impulse buying both simultaneously and partially. To the business manager matahari department store, it is important to make a comfortable environment for the customers to make them stay longer in the store and there will be more chances for unplanned purchases to happen which can give a huge contribution for the business. Keywords: hedonic motives, shop environment, impulse buying